Dermoscopic findings and assessment of treatment response in patients with tinea incognito: A pilot study - Sheetal Yadav; Deepika Pandhi; Chander Grover; Shukla Das (Wolters Kluwer Medknow Publications, 2024)
Background: Tinea incognito presents with atypical, widespread, and recurrent lesions. Dermoscopy can aid its rapid diagnosis. Aim and Objectives: This study aimed at assessing dermoscopic features and response to treatment in patients with tinea incognito. Materials and Methods: An evaluation of 62 patients with tinea of glabrous skin (Group A (cases)-31 steroid modified and Group B (controls)-31 treatment naïve) was done. Clinical, dermoscopic, and mycological evaluations were done for both groups at baseline, 2, and 4 weeks of terbinafine therapy. Clinical severity (Clinical Assessment Severity Score (CASS) and Visual Analogue Scale (VAS)) and frequency of various dermoscopic changes were compared at 0 and 4 weeks between cases and controls, using unpaired Student's t-test, Mann-Whitney U-test, and Wilcoxon signed-rank test. Results: Baseline dermoscopic features for both groups were significantly different with respect to frequency of broken hair, bent hair, micropustules and Morse code hair. Earliest feature to resolve with treatment was micropustules at 2 weeks. Significant reduction in frequency of morphologically altered hair was evident at 4 weeks. Telangiectasia, dotted vessels, I-hair, and broken hair persisted for a longer period of time. Terbinafine for 4 weeks was an effective treatment, producing complete cure in 73% of cases and 93% of controls. Persistent dermoscopic changes at 2 weeks were found to be associated with treatment failure at 4 weeks, highlighting the role of dermoscopy in identifying patients requiring prolonged treatment. Conclusions: Dermoscopy can be used as a diagnostic and monitoring tool for tinea of glabrous skin.